南極研究科学委員会の連続プランクトン採集器データベースグループワークショップ2016報告 - 高橋, 邦夫; タカハシ, クニオ; Kitchener, John A.; Robinson, Karen; Hosie, Graham W.; Takahashi, Kunio T. (国立極地研究所, 2017)
2016年12月12−16日にオーストラリア南極局にて「南極研究科学委員会（以下SCAR）連続プランクトン採集器（以下CPR）データベース専門家グループワークショップ2016」を開催した．南大洋CPR観測プロジェクトを主導する日本，オーストラリア，ニュージーランドの実務担当者の間で，観測データの品質管理，種同定やデータ分析手法の再確認，および今後の活動についての詳細な討議を行った．前半はこれまでのプロジェクト活動を総括し，各国のマネージメントの状況を確認し，さらには将来的な観測計画を議論した．後半は動物プランクトンの種同定リストの更新のため，具体的な分類カテゴリーの種同定を実施した．特に有孔虫とオキアミ類の幼生期について，確認を行った．まとめられた種同定基準を用いて新たなマニュアル作成を開始することになった．今後，2年に一度を目途にプロジェクト参加国の技術者を集めたワークショップを開催し，各国間で統一された試料処理およびデータ管理を維持していくことを目指すこととなった． The“Southern Ocean Continuous Plankton Recorder (SO-CPR) Survey Standards Workshop”was held at the Australian Antarctic Division on 12−16December 2016. The purposes of the workshop were to confirm that consistent and high standards of species identification, methodology, and data quality were being maintained amongst the main analysts in the SO-CPR Survey, and to discuss future training methods, including a SO-CPR manual that will include a counting rule book, and a future road map for the SO-CPR program. During the workshop we discussed a range of topics including: taxonomic resolution issues (particularly for Foraminifera and euphausiid larval identification and staging); laboratory methods (preservation and storage, with emphasis on maintaining correct pH); shipboard techniques; training methods; data handling (metadata, database, data sharing); gap analysis (spatial, temporal, data, quantitative); and future workshops/conferences, including comprehensive training workshops for emerging SO-CPR survey partners (India). We agreed that there should be a larger workshop every two years to ensure that the high standards of the SO-CPR program are maintained. departmental bulletin paper